Prepollex diversity and evolution in Cophomantini (Anura: Hylidae: Hylinae) - Pinheiro, Paulo D. P; Blotto, Boris L [UNESP]; Ron, Santiago R; Stanley, Edward L; Garcia, Paulo C. A; Haddad, Célio F. B [UNESP]; Grant, Taran; Faivovich, Julián (Oxford University Press (OUP), 2022)
Several species of Cophomantini are known to have an enlarged prepollex, commonly modified as an osseous spine. We surveyed the osteology and myology of the prepollex and associated elements of 94 of the 190 species of Cophomantini, sampling all genera, except Nesorohyla. Two distinct prepollex morphologies were found: a blade-shaped and a spine-shaped morphology. We described the observed variation in 17 discrete characters to study their evolution in the most inclusive phylogenetic hypothesis for Cophomantini. Both morphologies evolved multiple times during the evolutionary history of this clade, but the origin of the spine-shaped distal prepollex in Boana and Bokermannohyla is ambiguous. The articulation of metacarpal II with the prepollex through a medial expansion of the metacarpal proximal epiphysis is a synapomorphy for Boana. The shape of the curve of the spine, and a large post-articular process of the distal prepollex, are synapomorphies for the Boana pulchella group, the latter being homoplastic in the Bokermannohyla martinsi group. Muscle character states associated with the spine-shaped prepollex are plesiomorphic for Cophomantini. We discuss evolution, function, behaviour and sexual dimorphism related to the prepollical elements. A bony spine is associated with fights between males, but forearm hypertrophy could be more related with habitat than with territorial combat.
Keywords: carpus; comparative morphology; gladiator frogs; myology; osteology